The Potential of Poverty in the City of Palangka Raya: Study SMIs Affected Pandemic Covid 19 - Pipit Anggriati Ningrum; Alexandra Hukom; Saputra Adiwijaya (Budapest International Research and Critics University, 2020)
This study aims to analyze the increasing potential for poverty in the city of Palangka Raya from the perspective of SMIs due to the impact of the 19th COVID pandemic. The data was obtained based on the results of in-depth interviews from February to April 2020 with 10 SMIs and supported from secondary data from the Central Statistics Agency. The data is processed based on qualitative research principles based on the type of case study research. In the results of this study it was found that the SMIs experienced a very detrimental impact in terms of sales and marketing of products so that employees who come to work are terminated indefinitely, in this connection it appears that there is potential increases in poverty that can occur in the future come.